Asymptotic Normality of Single-Equation Estimators for the Case with a Large Number of Weak Instruments - Norman R. Swanson; John C. Chao (Rutgers University, Department of Economics, 2003)
This paper analyzes conditions under which various single-equation estimators are asymptotically normal in a simultaneous equations framework with many weak instruments. In particular, our paper adds to the many instruments asymptotic normality literature, including papers by Morimune (1983), Bekker (1994), Angrist and Krueger (1995), Donald and Newey (2001), Hahn, Hausman, and Kuersteiner (2001), and Stock and Yogo (2003).
Keywords: C13; C31; 330; CLT for bilinear forms; instrumental variables; k-class estimator; local-to-zero framework; pathwise asymptotics; weak instruments; Schätztheorie; Instrumentalvariablen-Schätzmethode; Theorie